2019
DOI: 10.3390/ijerph17010205
|View full text |Cite
|
Sign up to set email alerts
|

Cat and Dog Ownership in Early Life and Infant Development: A Prospective Birth Cohort Study of Japan Environment and Children’s Study

Abstract: Contact with companion animals has been suggested to have important roles in enhancing child development. However, studies focused on child development and pet ownership at a very early age are limited. The purpose of the current study was to investigate child development in relation to pet ownership at an early age in a nationwide prospective birth cohort study: the Japan Environment and Children’s Study. Associations between cat and dog ownership at six months and infant development at 12 months of age were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 45 publications
2
16
0
Order By: Relevance
“…Besides, previous research has shown that dog ownership has a positive effect on child development, so we considered it as a variable 24 . However, we found that pet ownership interfered with breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, previous research has shown that dog ownership has a positive effect on child development, so we considered it as a variable 24 . However, we found that pet ownership interfered with breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…The ASQ-3 is a set of well-validated, globally used questionnaires that is recommended by the United Nations Children’s Fund to identify potential delays and help determine which children need further assessment or ongoing monitoring [ 15 ]. The Japanese version of the ASQ-3 has also been validated [ 16 ] and has already been used in previous studies [ 17 , 18 , 19 ]. The ASQ-3 assesses the following five areas of development: (1) Communication: Language skills, such as babbling, vocalizing, listening, and understanding; (2) gross motor: Arm, body, and leg movements to move and play; (3) fine motor: Hand and finger movements; (4) problem solving: Problem-solving skills, learning, and playing with toys; (5) personal-social: Self-help skills, solitary social play, and play with toys and others.…”
Section: Methodsmentioning
confidence: 99%
“…We used the following variables as covariates for mothers: maternal age (<25, 25–<30, 30–<35 or ≥35 years), pre-pregnancy body mass index asked during the first trimester (<18.5, 18.5–<25 or ≥25 kg/m 2 ), parity (primipara or multipara), history of allergy measured during the first trimester (yes or no), Kessler Psychological Distress Scale (K6) score (<5, 5–12, ≥13) [ 20 , 21 , 22 ], smoking status (never, former, or current), alcohol intake (never, former, or current), number of hours spent outdoors (<1, 1–<2, 2–<3 or ≥3 h), physical activity corresponding to over 10 min of walking a day (yes or no), quintile of folic acid intake measured using food frequency questionnaire (≤153, 154–203, 204–257, 258–337 or ≥338 µg) [ 23 , 24 ], marital status assessed during the first trimester (married, single, divorced, or widowed), highest educational level (≤12, >12–<16 or ≥16 years), employment status (yes or no), and annual household income (<4, 4–<6 or ≥6 million Japanese Yen). As covariates for dwelling environment, we used type of residence (wooden detached house, steel-frame detached house, wooden multiple dwelling house/apartment, steel-frame multiple dwelling house/apartment, or other), number of rooms in the house or apartment (≤2, 3, 4, 5 or ≥6), living room flooring material ( tatami [Japanese straw floor covering], carpet on tatami, wooden flooring/tiles, carpet on wooden flooring/tiles, or other), having a pet (yes or no) [ 18 ], usage of air purifiers (yes or no) [ 17 ], age of house or apartment building (<1, 1–<3, 3–<5, 5–<10, 10–<20 or ≥20 years, or unknown), house renovation or interior completion after conception (yes or no), and number of years living in the current place of residence (<1, 1–<3, 3–<5, 5–<10, 10–<20 or ≥20 years). These covariates comprise the general and socio-economic status and dwelling environment as well as variables that have potential impact on exposure and outcome.…”
Section: Methodsmentioning
confidence: 99%
“…The other two papers analyzed ad hoc nationwide prospective birth cohorts set in Japan (Japan Environment and Children’s Study [ 22 ]) and the UK (UK Millennium Cohort Study [ 23 ]). Both the topics covered in these studies (co-sleeping associated with less breathing difficulties and child development in relation to pet ownership at an early age) could not be assessed through retrospective real word data.…”
mentioning
confidence: 99%
“…Both the topics covered in these studies (co-sleeping associated with less breathing difficulties and child development in relation to pet ownership at an early age) could not be assessed through retrospective real word data. The first manuscript used data from an ongoing nationwide prospective birth cohort study in Japan [ 22 ]. The recorded information is related to pregnant women who compiled the self-administered questionnaire between January 2011 and March 2014.…”
mentioning
confidence: 99%